2016
DOI: 10.1016/j.socscimed.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Place-based perceptions of the impacts of fracking along the Marcellus Shale

Abstract: We examined community perspectives and experiences with fracking in Doddridge County, West Virginia, USA as part of a larger assessment to investigate the potential health impacts associated with fracking in neighboring Maryland, USA. In November 2013, we held two focus groups with community residents who had been impacted by fracking operations and conducted field observations in the impacted areas. Employing grounded theory, we conducted qualitative analysis to explore emergent themes related to direct and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…The findings herein could be useful for further interpreting the burgeoning academic literature that links place attachment, place meanings, and place identity to extractive industries that transform rural communities (e.g., Perry 2012, Jacquet and Stedman 2013, Morrone et al 2015, Schafft and Biddle 2015, Fernando and Cooley 2016, Jerolmack and Berman 2016, Kroepsch 2016, Sangaramoorthy et al 2016). This emerging research broadly asserts that place attachment (an emotional bond between people and their environment) and place meanings (thoughts about what kind of place the focal environment is) strongly shape support for or opposition to extractive development.…”
Section: Discussionmentioning
confidence: 85%
“…The findings herein could be useful for further interpreting the burgeoning academic literature that links place attachment, place meanings, and place identity to extractive industries that transform rural communities (e.g., Perry 2012, Jacquet and Stedman 2013, Morrone et al 2015, Schafft and Biddle 2015, Fernando and Cooley 2016, Jerolmack and Berman 2016, Kroepsch 2016, Sangaramoorthy et al 2016). This emerging research broadly asserts that place attachment (an emotional bond between people and their environment) and place meanings (thoughts about what kind of place the focal environment is) strongly shape support for or opposition to extractive development.…”
Section: Discussionmentioning
confidence: 85%
“…The purpose of this study is to use survey data to further understand perceptions of crime and community in the context of the rapidly increasing and changing population in the Bakken region as well as how they relate to important factors such as residents' intentions to migrate and their views on oil and gas development. Existing studies have focused on how the perceived risk of social disruption or impacts may influence beliefs regarding future oil and gas development and vice versa (Evensen & Stedman 2017;Devine-Wright & Howes, 2010;Jacquet & Stedman, 2013;Sangaramoorthy et al, 2016), but have not examined how perceptions of crime impact attitudes about local energy development or intentions to migrate quantitatively.…”
Section: Crime and Perceptions Of Crime In Oil And Gas Boomtownsmentioning
confidence: 99%
“…Fracking fluids, for example, typically include friction reducers, surfactants, gelling agents, scale inhibitors, acids, corrosion inhibitors, antibacterial agents, and clay stabilizers, among other hazardous compounds, and are known to pose threats to plants, fish, aquatic life, and land animals (Gullion, 2015). Research has also shown exposure to fracking fluids to be associated with cancer, reproductive disruptions, skin, eye, and respiratory symptoms, impairments of the brain and nervous system, gastrointestinal and liver disease, as well as psychosocial stress (Finkel & Law, 2016;Sangaramoorthy et al, 2016).…”
Section: Fractured Communities: Risks and Impacts Associated With Uncmentioning
confidence: 99%
“…Indeed, fracking has drawn extensive criticism because of its greater social impacts than those incurred through conventional methods of energy development-particularly those related to the industrialization of rural areas, cost of living increases, differential economic benefits from signing royalties and leasing contracts, tensions between surface and mineral rights owners, increases in transient workers, crime, prostitution, rape, substance abuse, housing shortages, psychosocial stress, and diminished social capital (Brasier et al, 2011;Ellis et al, 2016;Hauter, 2016;Malin & DeMaster, 2016;Sangaramoorthy et al, 2016;Willow, 2014). Finally, other recent research suggests that natural gas fracking is not a ''climate-friendly alternative'' to coal and oil that will reduce our overall greenhouse gas footprint, nor will it help avert the growing threat of global warming and climate change that its advocates claim.…”
Section: Fractured Communities: Risks and Impacts Associated With Uncmentioning
confidence: 99%